Relationships of business strategies and organizational characteristics with innovation types: application in service companies - Ostos Mariño, Jhony; Saenz Arteaga, Arturo Rodolfo; Bremser, Kerstin (CEIPA Business School, 2019)
Various authors maintain that innovation practices depend on business strategies, therefore companies must configure an organizational structure that facilitates the coordination of tasks and allows objectives to be reached. In a sample of 203 service companies, an analysis was carried out of the influence of business strategies and organizational characteristics on technical innovation and administrative innovation. The results indicate that there is an important relationship between the business strategy and the technical and administrative innovations. On the other hand, organizational characteristics only had a significant relationship with technical innovation but not with the administrative innovation.

Varios autores sostienen que las prácticas de innovación dependen de las estrategias de negocio. Por consiguiente, las empresas deben configurar una estructura organizacional que facilite la coordinación de tareas y permita alcanzar los objetivos. En una muestra de 203 empresas de servicio se realizó un análisis de la influencia de las estrategias de negocio y de las características organizacionales en la innovación técnica y la innovación administrativa. Los resultados indican la existencia de una relación importante entre la estrategia de negocio y las innovaciones técnicas y administrativas. Además se encontró que las características organizacionales solo mostraron una relación significativa con la innovación técnica, pero no así con la innovación administrativa.
Keywords: Innovation types; Organizational characteristics; Tipos de innovación; Características organizacionales; Business strategy; Estrategias de negocio; https://purl.org/pe-repo/ocde/ford#5.02.04